2017
DOI: 10.1007/s13205-017-0660-6
|View full text |Cite
|
Sign up to set email alerts
|

A review on chimeric xylanases: methods and conditions

Abstract: Multi-functional enzymes are one of the nature's solutions to facilitate metabolic pathways, thus several reactions are regulated and performed simultaneously on one polypeptide chain. Inspired by nature, artificial chimeric proteins have been designed to reduce the production costs and improve the performance. One of the interesting applications of this method is in the plant-based industries such as feed additive, waste treatment, biofuel production, and pulp and paper bleaching. In fact, the heterogeneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A chimeric enzyme is commonly generated by fusing the GH catalytic domain obtained from one species with another protein domain such as a CBM from another species. In several studies, chimeric enzymes have been shown to improve the catalytic efficiency, thermostability, as well as substrate specificity (Oliveira et al, 2015;Saadat, 2017;Christensen et al, 2020;Gilmore et al, 2020).…”
Section: Designing New Chimeric Enzymes Inspired By the Domain Architmentioning
confidence: 99%
“…A chimeric enzyme is commonly generated by fusing the GH catalytic domain obtained from one species with another protein domain such as a CBM from another species. In several studies, chimeric enzymes have been shown to improve the catalytic efficiency, thermostability, as well as substrate specificity (Oliveira et al, 2015;Saadat, 2017;Christensen et al, 2020;Gilmore et al, 2020).…”
Section: Designing New Chimeric Enzymes Inspired By the Domain Architmentioning
confidence: 99%
“…To enhance xylanase production two major approaches are used, one involving genetic methods, the other at process level [24,84]. For some recent reviews, see [24,26,[84][85][86][87][88]. Some recent examples of genetic methods to enhance production levels include recombinant xylanase expression, which is particularly helpful when culturing the native strains is a complex task, constitutive expression through the use of a suitable promoter [89,90], and overexpression of xylanase by up-regulation of given genes [91] or codon optimization [92,93].…”
Section: Xylanolytic Marine Microorganismsmentioning
confidence: 99%
“…The GH11 endoxylanases have been extensively studied due to their potential for biotechnological applications, such as in the pulp and paper industries and for lignocellulose saccharification in biofuels production [39] . Although many synthetic MFPs fusing GH11s with catalytic domains have been constructed and tested (see Table 1, [43] ), few designed CBM-GH11 fusion proteins have been reported [29] , [56] . Using a knowledge-based approach from models of xylan packing on cellulose microfibrils to guide the construction of synthetic MFPs for lignocellulose mapping and degradation, here we describe the design, synthesis and expression of a stable and versatile scaffold protein based on tandem repeats of the left-handed β–3-prism structural motif, which we have named as the Beta Solenoid Scaffold (BeSS).…”
Section: Introductionmentioning
confidence: 99%